Rancang Bangun Prototype Sistem Deteksi Kebakaran Menggunakan Board EY1703 Berbasis Mikrokontroler STC15F2K32S2 - Fatrunadi, Dwi Abrar; Purwanti, Dwi (ELECTRON Jurnal Ilmiah Teknik Elektro, 2025)
Fires are common disasters in Indonesia, mainly caused by electrical short circuits and gas stove explosions, requiring an effective early detection system. While fire detection technology has improved, research on the reading speed of the STC15F2K32S2 microcontroller remains limited. This study evaluates the reading speed of the STC15F2K32S2 microcontroller in a fire detection system based on the EY1703 board, using flame and gas sensors as inputs and a buzzer and running LEDs as outputs. Tests were performed at distances from 5 cm to 20 cm with sensor tilt angles of 0°, 5°, and 10°. At a 0° tilt angle, the flame sensor reading time increased from 26.2 ms (5 cm) to 38.4 ms (20 cm), the buzzer from 44 ms to 61.8 ms, and the running LEDs from 48 ms (10 cm) to 29.2 ms (20 cm). At a 5° tilt angle, the flame sensor and buzzer reading times increased from 45.6 ms to 55.6 ms and from 49 ms to 63.8 ms, respectively, while the running LEDs remained stable at 43.6–52.8 ms. At a 10° tilt angle, the flame sensor time increased from 52.8 ms to 62.2 ms, the buzzer stayed between 48.2–56 ms, and the running LEDs increased from 32.8 ms to 61.2 ms. For gas detection, the average response times for CO, methane, LPG, and hydrogen were 53.4 ms, 47 ms, 47.6 ms, and 56.6 ms, respectively. Future research should explore additional sensors or IoT integration to improve detection speed and range.